Dampak Beban Kerja, Stres Kerja dan Time Management terhadap Work Life Balance Mahasiswa yang Bekerja pada kelas DLC Universitas Stikubank Semarang - Widya Dwi Hapsari; Kis Indriyaningrum (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the influence of workload, work stress, and time management on the work-life balance of students working in the DLC class at Stikubank University, Semarang. The sampling method was carried out using a saturated sample method for students from the Faculty of Economics and Business in the DLC Class of 2020. The results of the study showed that workload had a positive and significant influence on work-life balance, while work stress did not have a significant influence on work-life balance. . Apart from that, time management has also been proven to have a positive and significant influence on work-life balance. In conclusion, this research highlights the importance of workload management and time management in achieving balance between work life and personal life for students who work in the DLC classroom environment. Keywords: Workload, Work Life Balance, Time Management, Work Stress